2010
DOI: 10.1161/circulationaha.109.907717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonuniform Muscle Contraction on Sustainability and Frequency of Triggered Arrhythmias in Rat Cardiac Muscle

Abstract: Background-Arrhythmias are benign or lethal, depending on their sustainability and frequency. To determine why lethal arrhythmias are prone to occur in diseased hearts, usually characterized by nonuniform muscle contraction, we investigated the effect of nonuniformity on sustainability and frequency of triggered arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 71 publications
2
35
0
Order By: Relevance
“…Such regional differences in contractile strength may produce paradoxical stretching and shortening of the impaired muscle by contractions of the more viable neighboring muscle, thereby inducing Ca 2+ waves and triggered arrhythmias. 3, 44 The findings of the present study show that in the myocardium with non-uniform contraction, Cx43 plays some role in Ca 2+ wave propagation and the occurrence of arrhythmias, probably under the modulation of mitochondrial KATP channels, making Cx43 an attractive therapeutic target for suppressing triggered arrhythmias in such diseased hearts. 45,46 In conclusion, the present study suggests that Cx43 plays an affects ∆Ψm.…”
Section: Cbx and Ca 2+ Leak From The Srmentioning
confidence: 63%
“…Such regional differences in contractile strength may produce paradoxical stretching and shortening of the impaired muscle by contractions of the more viable neighboring muscle, thereby inducing Ca 2+ waves and triggered arrhythmias. 3, 44 The findings of the present study show that in the myocardium with non-uniform contraction, Cx43 plays some role in Ca 2+ wave propagation and the occurrence of arrhythmias, probably under the modulation of mitochondrial KATP channels, making Cx43 an attractive therapeutic target for suppressing triggered arrhythmias in such diseased hearts. 45,46 In conclusion, the present study suggests that Cx43 plays an affects ∆Ψm.…”
Section: Cbx and Ca 2+ Leak From The Srmentioning
confidence: 63%
“…Membrane potential was measured using ultracompliant glass microelectrodes and sarcomere length (SL) was measured using laser diffraction techniques, as previously described. 13 [Ca 2+ ]i was measured as previously described. 13, 15 Briefly, fura-2 pentapotassium salt was microinjected electrophoretically into each trabecula.…”
Section: Measurements Of Force [Ca 2+ ]I and Membrane Potentialmentioning
confidence: 99%
“…Muscle stretch increases myofilament Ca 2+ sensitivity and increases Ca 2+ binding to the myofilaments [12], thereby increasing the developed force [13][14][15]. Recently, it has been reported that muscle stretch increases the frequency of Ca 2+ sparks [16,17] due to production of reactive oxygen species (ROS) by the activation of NADPH oxidase in cardiac muscle [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ wave propagation is deeply involved in the occurrence of arrhythmias [14,19]. Ca 2+ waves are initiated not only by Ca 2+ leak from the sarcoplasmic reticulum (SR) under Ca 2+ overload [20] but also by Ca 2+ dissociation from the myofilaments under nonuniform contraction [15,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation